The Effectiveness of Oxytocin Hormone Massage in Increasing Breast Milk Production - Ellyzabeth Sukmawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
The aim of this study was to assess the impact of oxytocin massage on breast milk production in postpartum mothers. This research employed a quasi-experimental approach, specifically utilizing a pretest-posttest control group design. The study population consisted of all normal postpartum mothers receiving care at a Midwifery Independent Practice located in Kesugihan District, Cilacap Regency. A total of 30 participants were selected through purposive sampling. Data were analyzed using the Wilcoxon test to determine statistical significance. Prior to the intervention, the average breast milk production was measured at 22.82 cc/ml. Following the administration of oxytocin massage using fennel oil, the average milk volume significantly increased to 87.58 cc/ml. These results indicate that oxytocin massage is an effective intervention for enhancing breast milk production in postpartum mothers.